2014
DOI: 10.1590/s1516-8913201400025
|View full text |Cite
|
Sign up to set email alerts
|

Lead Nitrate Induced Testicular Toxicity in Diabetic and Non-Diabetic Rats: Protective Role of Sodium Selenite

Abstract: Among heavy metals, lead is one of the common pollutants found in the environment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
(50 reference statements)
2
9
0
1
Order By: Relevance
“…In our study the activities of CAT, SOD, GPx, and GST significantly enhanced in testis in lead nitrate and mercury chloride treated rats compared with normal rats. This finding is supported with the data of Apaydın et al [ 32 ]. Mercury chloride showed more toxicity than lead nitrate except GST activity.…”
Section: Discussionsupporting
confidence: 90%
“…In our study the activities of CAT, SOD, GPx, and GST significantly enhanced in testis in lead nitrate and mercury chloride treated rats compared with normal rats. This finding is supported with the data of Apaydın et al [ 32 ]. Mercury chloride showed more toxicity than lead nitrate except GST activity.…”
Section: Discussionsupporting
confidence: 90%
“…This situation is supported by a previous study (45). In addition, Apaydin et al (4) indicated in their study that lead nitrate treated diabetic rats were more sensitive than diabetic rats without lead nitrate treatment.…”
Section: Figure 6 (A) Liver Section Of Control Rats Cv: Central Veinsupporting
confidence: 61%
“…It causes morbidity and mortality due to the development of vascular complications like nephropathy and cardiovascular diseases. Owing to its quick global spread, diabetes mellitus is regarded as a considerable health problem (4).…”
mentioning
confidence: 99%
“…Heavy metals are commonly used generally in world and affect the function and damage the structure of many organs by causing oxidative damages (Garcia-Nino & Pedraza-Chaverri, 2014;Apaydin et al, 2015;Baş et al, 2015b). Lead and cadmium treatments are consistent with oxidative damage in various tissues (Merra et al, 2014;Djuric et al, 2015).…”
Section: Discussionmentioning
confidence: 99%